Groundwater springs in the German Wadden Sea tidal flat: A fast-track terrestrial transfer route for nutrients and dissolved organic matter - Carvalho da Silva, Roger; Seidel, Michael; Dittmar, Thorsten; Waska, Hannelore (Frontiers in Marine Science, 2023)
Submarine groundwater discharge (SGD) connects fresh groundwater and marine ecosystems and conveys terrestrially derived dissolved organic matter (DOM) and nutrients from land to sea. The connectivity of terrestrial and marine ecosystems via SGD depends strongly on local environmental settings. For example, SGD composition is modified on its transit through the coastal aquifer, with spring-type SGD from highly permeable aquifers presumably being less affected than diffuse discharge systems from sedimentary environments. In our study, we investigated spring-type SGD near Sahlenburg/Cuxhaven, Northern Germany, which passes through fine, unconsolidated tidal sediments before entering the coastal ocean. We characterized groundwater, surface water and seawater endmembers from different seasons and assessed the potential of tidal sediments impacting the biogeochemistry of “fast-track”, point-source groundwater discharge systems. In addition to physicochemical parameters and nutrients, we analyzed DOM molecular composition via ultrahigh-resolution mass spectrometry (FT-ICR-MS). Our data revealed a widespread physicochemical and geochemical influence of the groundwater springs on the tidal flat, producing low salinity and low dissolved organic carbon (DOC), but high nitrate and high oxygen concentrations not only in the springs, but also in adjacent porewater. From near- to offshore, salinity and DOC concentrations in springs decreased whereas nitrate and oxygen concentrations increased, resembling an inverse estuarine pattern. Furthermore, high nitrate values suggest anthropogenic sources (e.g., agricultural influence) in the surrounding watershed and may stimulate primary productivity in the tidal flat. Humic-like fluorescent DOM (FDOM) abundances and DOM molecular fingerprints indicated inputs of terrestrial DOM from nearshore saltmarsh plants, as well as from the nearby Elbe and Weser estuaries. Our study demonstrated that SGD had a strong geochemical impact even in the vicinity of large rivers, with productive springs actively hindering sulfate and nitrate reduction by flushing otherwise anoxic systems with oxygen. We posit that the geochemical influence of groundwater springs in tidal flats is underestimated because it can extend far beyond their visual discharge points.